PERAN MODAL SOSIAL DALAM USAHATANI TEBU DI DESA PARAPPUNGANTA KECAMATAN POLOMBANGKENG UTARA KABUPATEN TAKALAR - Ahmad, Rusnaeni; Syarif, Asriyanti; Mudatsir, Rasdiana (Institute of Computer Science (IOCS), 2025)
This study aims to determine the forms of trust, norms, and cooperation implemented in sugarcane farming in Parappunganta Village, North Polombangkeng District, Takalar Regency and to know the role of social capital in the development of sugarcane farming in Parappunganta Village, North Polombangkeng District, Takalar Regency. Informants were collected by purposive sampling or intentionally with several provisions. Qualitative analysis is a data analysis used by reducing, presenting data and drawing conclusions. The results illustrate that social capital strengthens the cooperative relationship between farmers and sugar factories, increases access to production resources and facilitates the exchange of information and technology in sugarcane farming. Trust and social norms encourage the formation of mutually supportive cooperation so as to create increased productivity and welfare. Challenges in managing social capital, such as inequality of access and dependence on certain parties that can affect the independence of farmers. The role of social capital in the development of sugarcane farming, namely: increasing sugarcane productivity, strengthening partnerships with sugar factories, and solving problems together.